PENERAPAN PROJECT BASED LEARNING UNTUK KETERAMPILAN BERBAHASA SISWA - Novie Wulandari; Pipit Nur Hidayati; Ervina Eka Subekti; Lilik Puji Rahayu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Language skills are fundamental competencies that elementary school students must possess to support literacy development and communication abilities. However, in first-grade Indonesian language learning, some students still experience difficulties in recognizing, reading, pronouncing, and writing simple vocabulary. This article aims to describe a best practice of implementing the Project Based Learning (PjBL) model on the topic of occupations vocabulary to improve students' language skills. The activity was conducted in Grade 1 of SD Supriyadi 02 involving 25 students. The method used was a best practice approach with a qualitative descriptive design. The learning process was carried out in three meetings through the stages of determining essential questions, planning the project, scheduling activities, implementing the project, presenting the results, and evaluating the learning experience. The project product was an occupation-themed diorama. Data were collected through observations, attitude assessments, skills assessments, and knowledge evaluation tests. The results showed that the implementation of the PjBL model improved students' activeness, communication confidence, ability to read occupation-related vocabulary, writing skills, and presentation skills in group work. The application of differentiated instruction and Universal Design for Learning (UDL) also helped accommodate the diverse learning needs of students. Therefore, Project Based Learning proved to be an effective approach for improving language skills among elementary school students.